2016
DOI: 10.1021/acsami.6b11431
|View full text |Cite
|
Sign up to set email alerts
|

Surface Surgery of the Nickel-Rich Cathode Material LiNi0.815Co0.15Al0.035O2: Toward a Complete and Ordered Surface Layered Structure and Better Electrochemical Properties

Abstract: A complete and ordered layered structure on the surface of LiNiCoAlO (NCA) has been achieved via a facile surface-oxidation method with NaSO. The field-emission transmission electron microscopy images clearly show that preoxidation of the hydroxide precursor can eliminate the crystal defects and convert Ni(OH) into layered β-NiOOH, which leads to a highly ordered crystalline NCA, with its (006) planes perpendicular to the surface in the sintering process. X-ray photoelectron spectroscopy and Raman shift result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 32 publications
(39 reference statements)
1
50
0
Order By: Relevance
“…Additionally, a preoxidization process before the high temperature calcination, which can largely promote the oxidation of Ni 2+ to Ni 3+ , has also been demonstrated to be an effective way to suppress the Li/Ni disordering . Typically, Wu and co‐workers have successfully synthesized the NCM811 cathode with dramatically decreased Li/Ni cation mixing under air atmosphere with an additional preoxidization process by using the nitrates …”
Section: Strategies To Mitigate the Surface/interface Structure Degramentioning
confidence: 99%
“…Additionally, a preoxidization process before the high temperature calcination, which can largely promote the oxidation of Ni 2+ to Ni 3+ , has also been demonstrated to be an effective way to suppress the Li/Ni disordering . Typically, Wu and co‐workers have successfully synthesized the NCM811 cathode with dramatically decreased Li/Ni cation mixing under air atmosphere with an additional preoxidization process by using the nitrates …”
Section: Strategies To Mitigate the Surface/interface Structure Degramentioning
confidence: 99%
“…5 (a). It has been reported that the smaller value of I (003)/ I (104), the larger the lattice disorder of material structure [45,46] . According to Fig.…”
Section: Structural Stability and Interfacial Properties Of Lncm811mentioning
confidence: 99%
“…After cycling at 1 C for 200 cycles, there exists one more semicircle in both of the two electrodes (Figure C). According to previous studies,, the semicircle located in high‐to‐medium frequencies corresponds to the resistance of Li + migrating through the surface film of the LNCAO materials (R sf ), while the semicircle at medium‐to‐low frequencies belongs to R ct and the inclined line located in low‐frequencies represents Z w . Note that before and after cycling, all of the resistance in the LNCAO/RGO, including R ct , R sf and Z w , are much lower than those of the LNCAO (Figure A and C).…”
Section: Resultsmentioning
confidence: 93%
“…synthesized LiNi 0.815 Co 0.15 Al 0.035 O 2 through pre‐oxidation of the commercial Ni 0.815 Co 0.15 Al 0.035 (OH) 2 precursors with the Na 2 S 2 O 8 . Their resulted LNCAO, with complete and ordered layered structures, exhibited improved electrochemical properties . Note that the phenomena of corrosions from the side reactions between LNCAO electrodes and the electrolytes are common and unavoidable in the cathodes .…”
Section: Introductionmentioning
confidence: 99%